2016
DOI: 10.5603/cj.a2015.0041
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary evaluation of the causes of cardiac tamponade: Acute and long-term outcomes

Abstract: Results: Cardiac tamponade was observed in 83 patients (52% females). Major etiologies included complications of percutaneous cardiac interventions (36%) and malignancies (primarily lung cancer; 23%), infectious/inflammatory causes (15%) and mechanical complications of myocardial infarction (12%). Sixteen (19%) patients died during the index hospitalization. Acute presentation of symptoms and lower quantity of effusion were associated with in-hospital mortality (p = 0.045 and p = 0.007). Tamponade secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…3 However, a recent study showed that iatrogenic complications were the most prevalent etiology for cardiac tamponade (36%). 4 Presentation may be rapid after chest wall trauma, aortic or cardiac rupture, or as a complication of cardiac procedures, necessitating prompt diagnosis and treatment. 4 Most reported cases of iatrogenic cardiac tamponade resulted from interventional procedures (e.g., percutaneous coronary intervention, transcatheter aortic valve implantation, pacemaker/implantable cardioverter-defibrillator implantation, arrhythmia ablation, and endomyocardial biopsy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, a recent study showed that iatrogenic complications were the most prevalent etiology for cardiac tamponade (36%). 4 Presentation may be rapid after chest wall trauma, aortic or cardiac rupture, or as a complication of cardiac procedures, necessitating prompt diagnosis and treatment. 4 Most reported cases of iatrogenic cardiac tamponade resulted from interventional procedures (e.g., percutaneous coronary intervention, transcatheter aortic valve implantation, pacemaker/implantable cardioverter-defibrillator implantation, arrhythmia ablation, and endomyocardial biopsy).…”
Section: Discussionmentioning
confidence: 99%
“…4 Presentation may be rapid after chest wall trauma, aortic or cardiac rupture, or as a complication of cardiac procedures, necessitating prompt diagnosis and treatment. 4 Most reported cases of iatrogenic cardiac tamponade resulted from interventional procedures (e.g., percutaneous coronary intervention, transcatheter aortic valve implantation, pacemaker/implantable cardioverter-defibrillator implantation, arrhythmia ablation, and endomyocardial biopsy). 5,6 To the best of our knowledge, we report the first case of intraoperative cardiac tamponade during hemihepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogen sokk általában myocardialis infarctus után alakul ki, emellett szívsebészeti beavatkozásokat követően, valamint számos sürgősségi sebészi kórkép (például hasi aortaaneurysma-ruptura), úgynevezett nem szívsebészeti invazív beavatkozások (non-cardiac surgical procedures -NCSP), szeptikus, vérzéses sokk után, intra-vagy poszt operatív szövődményeként is jelentkezik. 1 Cardiogen sokkot okozhat a szívsebészeti és invazív kardiológiai beavatkozások egyik legveszélyesebb szövődménye, a pericardialis tamponád is. A tamponád során a szívburokban leggyakrabban folyadék gyülemlik fel, amely lehet transsudatum vagy genny, de a klinikai gyakorlatban főleg a szívburokba történő vérzés okozhatja.…”
Section: Bevezetésunclassified
“…In recent years, the application of invasive cardiovascular procedures and the use of antiplatelet and anticoagulation drugs have increased in clinical medicine [ 1 ]. The risk of iatrogenic cardiac tamponade (CT) or pericardial effusion increases with the need for transseptal puncture and intraprocedural anticoagulation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%